Unveiling the diversity of Giant Neotropical Torrent frogs (Hylodidae): phylogenetic relationships, morphology, and the description of two new species. Issue 1 (31st December 2022) - de Sá, Fábio P.; Condez, Thais H.; Lyra, Mariana L.; Haddad, Célio F. B.; Malagoli, Leo R.
Abstract : The Neotropical family Hylodidae comprises 46 currently recognized rheophilic Torrent frog species, today classified in the genera Crossodactylus, Hylodes, Megaelosia, and Phantasmarana, all endemic to the Atlantic Forest. Megaelosia and Phantasmarana are distributed along the Serra do Mar and Serra da Mantiqueira mountain ranges, southeastern Brazil, and are the least speciose genera of the family, including all the mute giant hylodids. Megaelosia is a monotypic genus, whereas Phantasmarana comprises six currently recognized species: P. apuana, P. bocainensis, P. boticariana, P. jordanensis, P. lutzae, and P. massarti . Herein, we provide a taxonomic revision of these Giant Neotropical Torrent frogs, offering a comprehensively sampled species-level molecular phylogeny. By combining molecular and morphological data, we confirm that Megaelosia and Phantasmarana are valid genera. We provide diagnostic traits for both genera, redescribe the poorly known species P. jordanensis, and describe two new species from distinct localities at Parque Estadual da Serra do Mar, P. curucutuensis sp. nov. and P. tamuia sp. nov., presenting details of adult and larval morphology, and notes on their natural history and behaviour. We further discuss systematic and taxonomic concerns, and evolutionary processes related to distribution, body sizes, and communication in the family Hylodidae. http://zoobank.org/urn:lsid:zoobank.org:pub:61EA0116-6FB9-44B8-A2CE-E99D7B887E8B http://zoobank.org/urn:lsid:zoobank.org:act:079339E6-C802-4B47-A3A3-9FA0D0FCA3D1 http://zoobank.org/urn:lsid:zoobank.org:act:0EA22628-89E9-483B-AB90-F3F0D18E28F1